The morphology of permanent maxillary first molars evaluated by cone-beam computed tomography among a Yemeni population - Abdulbaset A. Mufadhal; Ahmed A. Madfa (BMC, 2023)
Abstract Background The study's objective was to use CBCT to ascertain the root and root canal anatomy of the permanent maxillary first molars in a Yemeni population. It was considered how gender affected the prevalence of root canal morphology. Methods A sample of 373 CBCT records of maxillary permanent first molars belonging to 373 Yemeni individuals (162 males and 211 females) aged between 12 and 65 years were included in this study. Using CBCT on the teeth, the root form and canal morphology for each root based on Vertucci's classification were evaluated. The distribution of MB2 occurrence was documented. The prevalence and resemblance of the men and females were investigated. The Chi-square test was performed to evaluate the findings. Results Of the 373 maxillary first molars studied, the three separated root form was found in 94.9% of the studied MFMs while the two fused and one separate root form was found in 4.5%. The majority of the three-rooted MFMs (82.6%) had more than three root canals (four canals in 77.2% and five canals in 5.4%). The prevalence of MB2 was as high as 82.3% of the three-rooted MFMs. Vertucci type II configuration was the most frequent canal type (25%) followed by Vertucci type III (23.1%) and Vertucci type I (17.7%) in the mesiobuccal root. Vertucci type I was the most prevalent canal configuration in the distobuccal root and palatal root of the three-rooted MFMs (96% and 99.5%, respectively). Conclusions The maxillary first molars' root canal morphology indicated notable variations among a Yemeni population. The maxillary first molars of most of the Yemeni participants in this study had three roots and four canals. In light of the high occurrence of MB2 (82.3%) in permanent maxillary first molars, our findings emphasize the need of searching for and using cutting-edge techniques to locate the MB2 canals. Males outnumbered females in proportion.